Speed - Visions of an Accelerated Age - Ballard, J.G.; Campbell, Nancy; Cendrars, Blaise; Dimendberg, Edward; George, Susan; Illich, Ivan; Kingwell, Mark; Lampert, Catherine; McQuire, Scott; Miller, Jeremy; Musil, Robert; Nasby, Judith; et al. (London : Whitechapel Art Gallery, 1998)
Lichtenstein, Roy ; Calvini, Italo ; Kawara, On ; Delaunay, Sonia ; Cendrars, Blaise ; Burden, Chris ; Jonas, Paul Ramirez ; Schwarz, Michiel ; Viriio, Paul ; Sugimoto Hiroshi ; McCracken, John ; Baart, Theo ; Chasnik, Ilya ; Kluin, Ivan ; Ruscha, Ed ; Wolff, Paul ; Renger-Patzsch, Albert ; Sander, August ; Minton, John ; Gertler, Mark ; Messenger, Tony ; Antonioni, Michelangelo ; Snow, Michael ; Porter, Edwin S. ; Eisenstein, Sergei ; Pudlat, Pudlo ; Manomee, Qavava ; Tuu'luuq, Marion ; Sickert, Walter Richard ; Matisse, Henri ; Duchamp, Marcel ; Riverhead (New York) ; Gabo, Naum ; Epstein, Jacob ; Hamilton, Richard ; Breuer, Marcel ; Picabia, Francis ; Leger, Fernand ; Boccioni, Umberto ; Le Corbusier ; Lewis, Wyndham ; Lissitzky, El ; Gursky, Andreas ; Bertelli, RA ; Nicolas, Christian ; Smithson, Robert ; Sachs, Wolfgang ; Boren, Mark Edelman ; Ruscha, Ed ; Celmins, Vija ; Nowotny, Helga ; Dibbets, Jan ; Graham, Rodney ; Weiner, Lawrence ; Leonov, Alexei ; Exter, Alexandra ; Demuth, Charles ; Creed, Martin
Speed - Visions of an Accelerated Age, Whitechapel Art Gallery, London, 11 September - 22 November 1998 ; The Photographers' Gallery, London, 19 September - 14 November 1998 ; Macdonald Stewart Art Centre, London, 24 September - 31 October 1998
Engels
boek